RELATIONSHIP BETWEEN CORPORATE IDENTITY AND CORPORATE REPUTATION: A CASE OF A MALAYSIAN HIGHER EDUCATION SECTOR - Bahtiar Mohamad; Hassan Abu Bakar; Nik Adzrieman Abdul Rahman (Institute of Research and Community Outreach - Petra Christian University, 2007)
Organizations need corporate identity for survival. This identity is developing through the projection of one positive image that will increase its public confidence about the quality and achievements of the organization. This paper attempts to identify corporate identity and reputations of Universiti Utara Malaysia from its future prospective clients. Specifically, this research test the relationship between corporate identity and corporate reputation based on a Malaysian higher education sector. Further tests were conducted to identify which corporate identity component will be a significant predictor of corporate reputation. It reveals that there is significant positive relationship between corporate identity and corporate reputation.